The Effect Of Coconut (Cocos nucifera) Water For Male Sex Reversal In Green Swordtail (Xiphophorus hellerii) - Rahmawati, Nur; Diniarti, Nanda; Affandi, Rangga Idris (Program Studi Budidaya Perairan Universitas Mataram, 2025)
Male green swordtail (Xiphophorus hellerii) is one of fish that is widely favored by the Indonesian people and included in the top ten exports of ornamental fish trade. Market demand for male green swordtail is increasing, so it is necessary to find a method that produces male in mass. One technique that can be used is sex reversal. One of the natural ingredients that can be used is coconut (Cocos nucifera) water. This study aims to analyze the effect of different concentrations of coconut water on the sexing of male green swordtail. This study was conducted ford 60 days in June-August 2023 at the Fish Production and Reproduction Laboratoryd, Aquaculture Study Program, Faculty of Agriculture, University of Mataram. The method used was an experiment using a Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications, namely without coconut water administration or control (P1); 20% ​​coconut water administration (P2); 40% ​​coconut water administration (P3); 60% ​​coconut water administration (P4). The results showed that the method of soaking coconut water with different concentrations for 24 hours had a significant effect (p < 0.05) on the percentage of male green swordtail and survival rate, while the growth in length and weight of the fish did not have a significant effect on each treatment, because the growth of the fish was influenced by the feed given. The best treatment was obtained in treatment P3 with a coconut water concentration of 40%, which produced 91.84% male fish with a survival rate of 89.52%.